Determination of melamine in milk using surface plasma effect of aggregated Au@SiO2 nanoparticles by SERS technique. (October 2016) - Li, Ruoping; Yang, Guanghong; Yang, Jingliang; Han, Junhe; Liu, Junhui; Huang, Mingju
Abstract: A simple and rapid method to detect melamine in liquid milk by Surface-enhanced Raman Scattering (SERS) technique was presented. The pretreatment procedure of milk samples only contains hydrochloric acid treatment and twice centrifugation. In order to reduce the distortion about the Raman signals originating from charge transfer and electronic tunnelling effect, SiO2 shell-isolated gold nanoparticles (Au@SiO2 NPs) instead of Au NPs were employed to enhance signal intensity. Aggregation occurs when the Au@SiO2 NPs colloid is mixed with the melamine solution or the treated milk containing melamine. Different from aggregated Au NPs, these aggregated Au@SiO2 NPs on Cu substrate can undistortedly enhance the Raman signals of melamine using surface plasma effect. Quantitative analysis was tried and the results showed a good linearity (R 2 ≈ 0.99) when the melamine concentration was between 0.5 mgL −1 and 5 mgL −1 . The detection sensitivity satisfies the requirement of the Codex Alimentarius Commission and this method can be practically used for melamine detection in milk. Highlights: The pretreatment of milk sample is simple and rapid. Au@SiO2 NPs colloid can be preserved for a long time. The corresponding Raman signals are not distorted and their analysis is easy. It has a good linearity (R 2 ≈ 0.99) in quantitative analysis of melamine. The cost of the involved materials is less than 0.2 USD.